The Existence of the Iwadh Tradition in Strengthening the Relationship Between Congregations of Arabic Village in Manado - 'Ain, Aufa Qutratu (Lembaga Yasin AlSys, 2023)
Iwadh tradition is also important given to strengthen the relationship between congregation of Arabic Village in Manado. This phenomenological research aims to know the implementation of Iwadh Tradition reviewed from sociological approaches and to know the meaning of the implementation of Iwadh tradition in maintaining it’s existence and strengthening the silaturahim rope between pilgrims in Manado’s Arab Village. The participants in this research were one of the community leaders and Imam of the Masyhur Istiqlal Mosque in Manado Arab Village. This mini research conducted by the researcher uses a qualitative research type with a sociological approach. The results found that iwadh tradition known as the concept of close brotherhood, which has developed and become a symbol for the Arab Village community in the social sphere of the Manado City community, which is marked by the involvement of people from other villages or even urban villages who participate in and enliven the tradition encouraging Iwadh, so that it can strengthen the relationship between followers of religions. There for, The iwadh tradition has a meaning as an expression of a servant's gratitude to Allah SWT with the completion of the fasting month of Ramadhan.